Renal venous Doppler ultrasound – a new parameter for predicting outcomes in patients with decompensated heart failure - Zh. D. Kobalava; A. F. Safarova; R. Sh. Aslanova; M. V. Vatsik-Gorodetskaya (Бюллетень сибирской медицины, 2023)
Aim. To assess the frequency, dynamics, and prognostic value of renal venous congestion using Doppler ultrasound in patients with decompensated heart failure (DHF).Materials and methods. A prospective, single-center study included 124 patients with DHF (mean age 70 ± 12 years, 51.6% were males), left ventricular ejection fraction (LVEF) 44 [34; 55] %, N-terminal pro B-type natriuretic peptide (NT-proBNP) 1,609 [591; 2,700] pg / ml. All patients underwent a standard physical examination and laboratory and instrumental tests, including the assessment of the NT-proBNP level. Renal venous blood flow was assessed using pulsed-wave Doppler ultrasound. The presence of continuous renal blood flow was considered as the absence of venous congestion, while intermittent blood flow (two-phase and single-phase flow) indicated venous congestion. Rehospitalization for DHF and reaching a composite endpoint (rehospitalization for DHF and cardiovascular mortality) within 12 months after discharge were selected as endpoints.Results. At admission, continuous renal venous blood flow was observed in 34 (27.4%) patients, intermittent renal venous blood flow was found in 90 (72.6%) patients: two-phase flow in 62 (50%) and single-phase flow in 28 (22.6%) patients with DHF. At discharge, 66 (53.2%) patients had intermittent renal venous blood flow: two-phase flow in 50 (40.3%) and single-phase flow in 16 (12.9%) patients. Correlations of renal venous congestion with the levels of NT-proBNP, serum iron, uric acid, creatinine, LVEF, systolic pressure in the pulmonary artery (SPPA), and the development of acute kidney injury (AKI) were revealed. Persistent renal venous congestion at discharge was significantly associated with a higher probability of rehospitalization for DHF (hazard ratio (HR) 1.93 95% confidence interval (CI) (1.017–3.67); p = 0.044) and a composite endpoint (HR 2.66, 95% CI (1.43–4.96); p = 0.002).Conclusion. In patients with DHF, it is necessary to evaluate renal venous blood flow using pulsed-wave Doppler ultrasound to stratify patients with development of cardiovascular complications within 12 months.